The Effectiveness of E-Books in Learning: An Analysis of Trends in Elementary Schools - Saptono, Bambang (Jurnal Prima Edukasia, 2023)
Less than optimal student learning outcomes are a problem experienced by teachers in elementary schools. It is evidenced by the student learning outcomes that have not been maximized. The objective of this study is to provide a comprehensive description of the effectiveness of incorporating e-books into the learning process. This study used a quantitative approach with a time series design. The research subjects consisted of elementary school students and teachers. The student subjects involved came from the fifth-grade level. Data collection was done by testing and observation. Data analysis was performed by testing four trend models. These are the Linear Trend Model, Quadratic Trend Model, Growth Curve Model, and S-Curve Trend Model. The research findings indicate that e-books are a viable tool for facilitating learning in elementary school settings. It is based on the positive trend shown in student learning outcomes after applying the e-book as a learning tool. It strengthens the recommendation regarding implementing e-books by teachers to maximize student learning outcomes.